Test Results From the Prelaunch Characterization Campaign of the Engineering Test Unit of the Ocean Color Instrument of NASA’s Plankton, Aerosol, Cloud and Ocean Ecosystem (PACE) Mission - Meister, Gerhard; Knuble, Joseph J.; Chemerys, Leland H.; Choi, Hyeungu; Collins, Nicholas R.; Eplee, Robert E.; Gliese, Ulrik; Gorman, Eric T.; Jepsen, Kim; Kitchen-McKinley, Samuel; Lee, Shihyan; Mcintire, Jeffrey W.; et al. (Frontiers in Remote Sensing, 2022)
This paper summarizes the results from the system level test campaign of the Engineering Test Unit (ETU) of the ‘Ocean Color Instrument’ (OCI), the primary payload of NASA’s ‘Plankton, Aerosol, Cloud and ocean Ecosystem’ (PACE) mission. The main goals of the test campaign were to optimize characterization procedures and evaluate system level performance relative to model predictions. Critical performance parameters such as radiometric gain, signal-to-noise ratio, polarization, instantaneous field-of-view, temperature sensitivity, relative spectral response and stability were evaluated for wavelengths from 600 to 2,260 nm and are in line with expectations. We expect the OCI flight unit to meet the PACE mission performance requirements. Building and testing the ETU has been extremely important for the development of the OCI flight unit (e.g. improved SNR by increasing the aperture, optimized thermal design), and we strongly recommend the inclusion of an ETU in the development of future spaceborne sensors that rely on novel technological designs. ETU testing led to the discovery of a hysteresis issue with the SWIR bands, and a correction algorithm was developed. Also, the coregistration of the SWIR bands relative to each other is worse than expected, but this was discovered too late in the schedule to remediate.